LE ROLE SOCIAL DES PERSONNES AGEES AU DEBUT DU XXIe SIECLE - Carmine Clemente (European Scientific Journal, ESJ, 2014)
European policies for active and healthy aging aims to raise awareness of the contribution of older people to society. Their social role is significantly related to participation, or not, to work and production systems.